The peculiar nature of habit - Murphy, Verda Ellen (My University, 1906)
Introduction: Take pains in planting a tree so as to get it started to growing straight then bend it over, “It will not stay there,” you say, this may represent good habits as it is a straight tree one would desire. Now then plant a tree so it will grow crooked then bend it up straight it will not stay there no more than the other would stay crooked, this may represent bad habits; we see that the crooked tree is as persistent as the straight one. That is good habits and bad habits have the same strong tendency toward their own individual course. When we look at living creatures from the same outward point of view as the tree the first thing we see is that they are “bundles of habits,” and these habits act in the same way as they did in these two different trees. The habits of wild animals that are implanted at birth are called instincts, while the habits of man are obtained more from education and are called, by some, habits of reasoning. So we can see that the field of habit covers a very large part of life, and we are bound at the outset to clearly define our subject.
Citation: Murphy, Verda Ellen. The peculiar nature of habit. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Habits; Psychology; Theses; Manuscripts (documents)